Study of Mismatch Repair Protein Expression by Using Immunohistochemistry in Various Carcinomas with Special Reference to Colorectal Adenocarcinomas - At a Tertiary Referral Laboratory in India - Lachit, Kalita; Vinita, Pant (Asian Pacific Journal of Cancer Biology, 2022)
Background: DNA mismatch repair (MMR) is an important process during the DNA replication for correcting DNA replication errors. Deficient MMR (dMMR) leads to increased mutational burden and has been associated with several carcinomas and cancer syndromes like Lynch syndrome. The absence of MMR protein by immunohistochemistry is a surrogate marker for microsatellite instability. The aim of the study is to present our datas of MMR deficient tumors and the pattern of MMR protein loss by using immunohistochemistry,also to highlight the technical issues of tissue processing that interfere in result interpretation. Material & Method: 318 cases of various carcinomas were analysed for mismatch repair proteins viz. MLH1, MSH2, MSH6 and PMS2 using immunohistochemistry. Result: Out of total 318 cases,47 cases showed deficient MMR proteins. Among the MMR deficient cases colonic adenocarcinoma cases has the highest percentage with loss of MMR proteins. Regarding pattern of MMR protein loss the simultaneous loss of both MLH1 and PMS2 is the most common pattern. In 5 cases (1.5%) of total cases we could not interpret the result. In compare to MMR proficient colorectal adenocarcinomas, the MMR deficient tumors are predominantly right sided and on histopathology they shows high grade histology,intratumoral lymphocytic infiltration, peritumoral lymphocytic infilatration, mucinous and signet cell components. Conclusion: Evaluation of MMR proteins using immunohistochemistry is relatively easy to institute in the routine testing as it is a useful predictive and prognostic marker in various carcinomas,also it helps screening the cases of lynch syndrome. This study also highlight the need of using standard protocols for tissue fixation and processing before evaluating for MMR proteins.